(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
In this research, the subject of accounting information system was used to improve the marketing activity and its’ significance through addressing each of the accounting system and marketing activity. The accounting system represents one of the important systems because it provides the necessary information for the company to take administrative decisions. The marketing activity represents one of the important activities to find a set of benefits, such as locative and symbolic benefits; also it contributes to find formalism benefit by providing the requirements of customers for the production management or the design. The goal was to use the accounting information system to support the marketing activity by providing the necessary information for it.